2017
DOI: 10.3892/etm.2017.5019
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA AK023948 enhances tumor progression in hepatocellular carcinoma

Abstract: The long non-coding RNAs (lncRNAs) have been demonstrated to play pivotal roles in a broad range of processes including tumor biology. However, the exact contributions of lncRNAs to hepatocellular carcinoma (HCC) remain poorly defined. In current study, we have unraveled a novel function of AK023948 in HCC. We found that AK023948 was substantially upregulated in tumor tissues. Meanwhile, higher AK023948 expression correlated with poor survival. Upregulation of AK023948 expression can promote HepG2 and Hep3B pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The reaction was performed with incubation at 42°C for 1 h, and the enzyme was subsequently inactivated by incubation at 85°C for 5 min. The total reaction volume was 20 µl and the mixture was prepared as previously described (16). For qPCR, the PCR solution contained 1 ml cDNA, 1 ml primers and 10 ml SYBR Green and 5 ml RT-qPCR Master mix (all from Invitrogen; Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was performed with incubation at 42°C for 1 h, and the enzyme was subsequently inactivated by incubation at 85°C for 5 min. The total reaction volume was 20 µl and the mixture was prepared as previously described (16). For qPCR, the PCR solution contained 1 ml cDNA, 1 ml primers and 10 ml SYBR Green and 5 ml RT-qPCR Master mix (all from Invitrogen; Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…The lncRNAs are involved in a variety of biological processes, including proliferation, differentiation, autophagy, and apoptosis 810. In the field of cancer research, lncRNAs have been found to regulate the progression of various types of cancers such as glioma,11 breast cancer,12 colorectal cancer,13 liver cancer,14 and leukemia15 and are associated with recurrence and poor prognosis. A large number of dysregulated lncRNAs have been identified in gastric cancer till now 16.…”
Section: Introductionmentioning
confidence: 99%
“… 8 10 Therefore, it is urgent to explore new regulating mechanisms for HCC progression to identify more therapeutic targets for HCC treatment. 11 13 …”
Section: Introductionmentioning
confidence: 99%